Past performance may be a guarantee of future results - Bevers, Alexia (2019)
Background: Sam Stovall, author of The Seven Rules of Wall Street: Crash-Tested Investment Strategies That Beat the Market, has an investment strategy called There’s Always a Bull Market Someplace (Stovall, 2009). Hypothesis: Though one of the frequently-heard sayings in finance is, “Past performance is not a guarantee of future results,” this study seeks to see how this investment strategy, specifically in regard to sectors, has done over the last 10 years since Stovall published his book. Methodology: Sector performance data, specifically 12-month leading price performance, is used to calculate risk, risk-adjusted return, compound annual growth rate, and the frequency of beating the S&P 500. The top 3 sectors should be held in a portfolio until the sector falls out of the top 3, and then the new sector that has reached the top 3 will be added to the portfolio. The portfolio should be updated each month. Expected Results: This investment strategy is expected to have higher returns than the S&P 500 more than 66% of the time, indicating that it is a useful investment strategy. Conclusion: This study will attempt to show that investors who took Stovall’s advice in 2009 could have had healthy returns on their investment and analyze how much those returns could have been.